New‐onset type 1 diabetes and Graves' disease after antiretroviral therapy in a patient with human immunodeficiency virus infection. Issue 3 (10th January 2023) - Taguchi, Maho; Ihana‐Sugiyama, Noriko; Shiojiri, Daisuke; Izumi, Kazuo; Kobayashi, Michi; Kodani, Noriko; Bouchi, Ryotaro; Ohsugi, Mitsuru; Tanabe, Akiyo; Ueki, Kohjiro; Kajio, Hiroshi
Abstract: Patients with human immunodeficiency virus (HIV) infection receiving antiretroviral therapy can develop autoimmune diseases, referred to as immune‐inflammatory reconstitution syndrome. Nevertheless, only a few reports on the onset of type 1 diabetes as immune‐inflammatory reconstitution syndrome are available. A 40‐year‐old Japanese man with HIV infection was initiated with antiretroviral therapy at the age of 29 years. He developed Graves' disease at 35 years and diabetes, with a hemoglobin A1c of 6.5%, and maintained insulin secretion at 38 years. His antiglutamic acid decarboxylase antibody level was >2, 000 U/mL, and he was diagnosed with slowly progressive type 1 diabetes. At the age of 40 years, he was admitted to our hospital with diabetic ketosis. We retrospectively assayed his stored plasma samples for thyroid‐stimulating hormone receptor antibody and antiglutamic acid decarboxylase antibody, which showed positive conversion after initiating antiretroviral therapy, suggesting that Graves' disease and type 1 diabetes developed as a probable result of immune‐inflammatory reconstitution syndrome. Abstract : Human immunodeficiency virus patients receiving antiretroviral therapy can develop immune‐inflammatory reconstitution syndrome. Type 1 diabetes is an autoimmune disease, but type 1 diabetes is rarely reported as immune‐inflammatory reconstitution syndrome. In this article, we report a case of combined Graves' disease and type 1 diabetes after antiretroviral therapy initiation with possible immune‐inflammatory reconstitution syndrome with previous case series.